Home Leaving and Risk Taking Behaviors of Youth: The Case of Zamboanga Peninsula - Echem, Rosalyn R.; Mateo, Grace R.; Sorita, Jasmin (JPAIR Multidisciplinary Research, 2008)
The study examines the risk-taking behaviors of young adults aged 15-24 in the Zamboanga Peninsula who have experienced living away from home, identifying significant factors influencing their engagement in non-sexual and sexual risk behaviors and proposing possible interventions. Findings reveal more females have lived away from home than males, yet males exhibit higher levels of smoking, drinking, drug use, and premarital sex. Multivariate analysis identifies age, schooling status, participation in religious activities, and urban exposure as risk factors for smoking among females, though religiosity provides a protective effect. For home-leavers, both males and females are twice as likely to drink as non-home-leavers. Increasing age and urban exposure predispose male adolescents to drug use, while age, marital status, urban exposure, and employment increase the likelihood of premarital sex (PMS). However, being in school protects adolescents from engaging in PMS. The study also highlights the interconnectedness of sexual and non-sexual risk behaviors. Smoking significantly increases the odds of drinking for both sexes—male smokers are six times more likely to drink, while female smokers are five times more likely. Additionally, smoking and drinking heighten the likelihood of drug use by five times or more for both sexes. Those who smoke and use drugs are also more likely to engage in premarital sexual behavior. These findings underscore the need for targeted interventions addressing these behaviors through education, community programs, and policies aimed at mitigating risk factors while promoting protective influences like religiosity and school attendance.
Keywords: Home Leaving; Risk Taking